2016
DOI: 10.1093/cpe/bzw004
|View full text |Cite
|
Sign up to set email alerts
|

Classical Theory of Investment: Panel Cointegration Evidence From 13 EU Countries

Abstract: In the realm of macroeconomic theory, it is well established that investment decisions play an instrumental role in the determination of the level of output and employment; nevertheless, little progress has been made in relation to the theoretical aspects of these decisions. This paper, inspired by the classical approach to capital accumulation as well as the Keynesian theory of effective demand, attempts to enhance our empirical understanding of what determines investment decisions by exploring profitability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…In recent years, a number of unit root tests have been developed, such as those by Levin, Lin, and Chu (2002), Im, Pesaran, and Shin (2003), among other, which are shown to be more powerful than the unit root tests applied to individual series. Although these tests are commonly termed "panel unit root" tests, theoretically speaking, they are simply multiple-series unit root tests that have been applied to panel data structures (Alexiou, Tsaliki, & Tsoulfidis, 2016). In this study, we utilize both common root tests-Levin, Lin, Chu-and individual root tests-Im, Pesaran, Shin and ADF, Fisher.…”
Section: Model Specificationmentioning
confidence: 99%
“…In recent years, a number of unit root tests have been developed, such as those by Levin, Lin, and Chu (2002), Im, Pesaran, and Shin (2003), among other, which are shown to be more powerful than the unit root tests applied to individual series. Although these tests are commonly termed "panel unit root" tests, theoretically speaking, they are simply multiple-series unit root tests that have been applied to panel data structures (Alexiou, Tsaliki, & Tsoulfidis, 2016). In this study, we utilize both common root tests-Levin, Lin, Chu-and individual root tests-Im, Pesaran, Shin and ADF, Fisher.…”
Section: Model Specificationmentioning
confidence: 99%
“…We are of the view, however, that the underlying cause of the supplyside turbulence should also be sought in the realms of the Marxian tradition that relates productive investment with dwindling profitability (see Marx, 1990 translated edition of Marx 1867). In particular, profitability, which is the ultimate driver of productive investment and growth in capitalist economies, has dropped dramatically to near historic lows, leading to decreased levels of industrial output, international trade, investment expenditure, and real GDP growth (see for instance, Alexiou and Trachanas, 2020;Alexiou, et al, 2016). As such, capitalist economies were plagued with anaemic economic growth well before the onset of the COVID-19 pandemic, and obviously long before the military conflict between Russia and Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more powerful unit root tests have been proposed – such as those by Levin et al (2002), Im, Hashem Pesaran and Shin, 2003 and Hadri (2000) – which are shown to perform more efficiently than the unit root tests applied to individual series. According to Alexiou, et al (2016), while these tests are commonly termed “panel unit root” tests, theoretically speaking, they are simply multiple-series unit root tests that have been applied to panel data structures (where the presence of cross-sections generates “multiple series” out of a single series) (p. 47). In this paper, both common and individual unit root tests have been utilized, that is, Levin, Lin, Chu (LLC), Im, Pesaran, Shin (IPS), Fisher–ADF and Fisher–PP.…”
Section: Methodsmentioning
confidence: 99%